Ragam desain interior modern / / Andie A. Wicaksono, Dimas Kharisma Yunizar, Suparno Sastra M. - ANDIE A. WICAKSONO ; Dimas Kharisma Yunizar ; Suparno Sastra M. (Griya Kreasi, 2014)
139 hlm. : : ilus. ; ; 22 cm [3 eks.]